2020
DOI: 10.3390/ijerph17113990
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Overall Participation Profile of Youth with Physical Disabilities Following the PREP Intervention

Abstract: The Pathways and Resources for Engagement and Participation (PREP), an environmental-based intervention, is effective in improving the participation of youth with disabilities in specific targeted activities; however, its potential impact on overall participation beyond these activities is unknown. This study examined the differences in participation levels and environmental barriers and supports following the 12-week PREP intervention. Existing data on participation patterns and environmental barriers and sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…A study on one environmental-based intervention showed that PEM-CY can capture improvements in children with physical disabilities. We will explore whether PEM-CY can capture postintervention changes in our study 64…”
Section: Methodsmentioning
confidence: 99%
“…A study on one environmental-based intervention showed that PEM-CY can capture improvements in children with physical disabilities. We will explore whether PEM-CY can capture postintervention changes in our study 64…”
Section: Methodsmentioning
confidence: 99%
“…55 Systematic reviews are available to support the effectiveness of specific types of intervention. 22 , 39 , 40 , 41 , 42 , 43 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 However, it is essential that practitioners understand the mechanisms of action of interventions and use their clinical judgement to identify which interventions target specific barriers and will therefore be effective in supporting an individual's goal attainment. 67 …”
Section: Stages Of the Sports Participation Frameworkmentioning
confidence: 99%
“… 5 Identifying and minimising these barriers, as well as building family support have been shown to be promising intervention strategies to improve the participation of individuals with CP. 12 Thus, it is possible that Sports Stars would be more effective if combined with an intervention which addressed these environmental barriers.…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggest that inadequate community facilities, few availabilities of sports programmes for different age groups, lack of equipment, limited transportation, physical inaccessibility, geographical location, financial constraints, lack of information available for families and attitudinal factors are significant barriers for children with CP to participate in sports and physical recreation 5. Identifying and minimising these barriers, as well as building family support have been shown to be promising intervention strategies to improve the participation of individuals with CP 12. Thus, it is possible that Sports Stars would be more effective if combined with an intervention which addressed these environmental barriers.…”
Section: Introductionmentioning
confidence: 99%